Physicochemical properties and antibacterial activity of essential oil fractions obtained from fresh Litsea angulata leaves - PUTRI, AGMI SINTA; NUR, MUHAMMAD; KUSUMA, IRAWAN WIJAYA; EGRA, SAAT; KUSPRADINI, HARLINDA (Nusantara Bioscience, 2025)
Abstract. Putri AS, Nur M, Kusuma IW, Egra S, Kuspradini H. 2025. Physicochemical properties and antibacterial activity of essential oil fractions obtained from fresh Litsea angulata leaves. Nusantara Bioscience 17: 96-102. Litsea angulata (Lauraceae) is widely grown in Kalimantan Island and is traditionally used as a medicinal plant. This work aimed to analyze the characteristics of the physicochemical from L. angulata oil fractions and the potency of its antibacterial activity. Litsea angulata fresh leaves were distilled, and their oil fractions were obtained by simple fractional distillation using water and steam distillation methods. The fraction of essential oil is based on the different distillation times. In this experiment, the following distillation periods were tested: 0-60 min, 60-120 min, and 120-180 min. The yield and color determined the physicochemical properties, while the chemical properties, as their compositions, were analyzed by GC-MS. The agar diffusion method was employed to assess antibacterial activity. Two kinds of synthetic standards, including chlorhexidine and chloramphenicol, were used to compare their antibacterial properties. Streptococcus sobrinus, Streptococcus mutans and Staphylococcus aureus were the microorganisms used in this investigation. The results showed fractions yield (range 0.09-1.66%) reached a maximum in 0-60 min, and color clearness. All oil fractions have various colors and chemical components according to their treatments. The diameter inhibition against selected bacteria (range 10.22-15.11 mm) was highest at fraction 0-60 min. This essential oil is potentially developed in the pharmaceutical industry as a natural alternative product.